2009
DOI: 10.1002/jmv.21592
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus DNA detected in peripheral blood samples from healthy Australian male blood donors

Abstract: Recent studies have shown that human papillomavirus (HPV) DNA can be found in circulating blood, including peripheral blood mononuclear cells (PBMCs), sera, plasma, and arterial cord blood. In light of these findings, DNA extracted from PBMCs from healthy blood donors were examined in order to determine how common HPV DNA is in blood of healthy individuals. Blood samples were collected from 180 healthy male blood donors (18-76 years old) through the Australian Red Cross Blood Services. Genomic DNA was extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 28 publications
5
66
2
3
Order By: Relevance
“…Additionally in two separate studies, HPV-16 was found to be present in breast tumors that occurred in European women with HPV-16 associated cervical cancer [Hennig et al, 1999b;Widschwendter et al, 2004], thus raising the possibility that HPV may be transmitted by hand from the female perineum to the breast. However recent evidence has been demonstrated for the hematological carriage of HPV on peripheral blood mononuclear cells which could provide an alternative pathway for the transmission of the virus to the breast [Bodaghi et al, 2005;Chen et al, 2009].…”
Section: Discussionmentioning
confidence: 97%
“…Additionally in two separate studies, HPV-16 was found to be present in breast tumors that occurred in European women with HPV-16 associated cervical cancer [Hennig et al, 1999b;Widschwendter et al, 2004], thus raising the possibility that HPV may be transmitted by hand from the female perineum to the breast. However recent evidence has been demonstrated for the hematological carriage of HPV on peripheral blood mononuclear cells which could provide an alternative pathway for the transmission of the virus to the breast [Bodaghi et al, 2005;Chen et al, 2009].…”
Section: Discussionmentioning
confidence: 97%
“…This was anticipated as papillomavirus infects squamous epithelial cells (de Villiers et al, 2004;White & Howley, 2013) and is often considered to be non-circulatory (Howley & Lowy, 2007), although some authors report the detection of papillomavirus in blood and other non-epithelial cell types (Yaguiu et al, 2008;Chen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…BPV-1/-2 E5 DNA has been detected in PBMCs of cattle suffering from urothelial tumours of the urinary bladder and horses affected by sarcoids (Brandt et al, 2008). Furthermore, the expression of BPV-2 E5 oncoprotein has been shown in PBMCs of haematuric cattle by both RT-PCR and Western blotting; immunocytochemical investigations on cytospin preparations from PBMCs showed that E5 was localized mainly in the cytoplasm of lymphocytes .Although further epidemiological studies are required to improve our understanding of PV transmission (IARC, 2007), it has been suggested that PBMCs may be PV carriers and blood may be a potential new route of transmission (Bodaghi et al, 2005;Chen et al, 2009;Roperto et al, 2008).In this report, we have clearly documented expression of the BPV-2 E5 oncoprotein and L1 capsid protein in PBMC subsets derived from cows affected by urinary bladder tumours.This study shows, for the first time, which blood cell subpopulations are involved in the potential spread of the virus by the bloodstream and that productive infections by BPVs can take place in PBMCs. …”
mentioning
confidence: 99%